2015
DOI: 10.1016/j.vetimm.2015.08.008
|View full text |Cite
|
Sign up to set email alerts
|

Two novel neutralizing antigenic epitopes of the s1 subunit protein of a QX-like avian infectious bronchitis virus strain Sczy3 as revealed using a phage display peptide library

Abstract: The spike (S) protein of the infectious bronchitis virus (IBV) plays a central role in the pathogenicity, the immune antibody production, serotype and the tissue tropism. In this study, we generate 11 monoclonal antibodies (mAbs) against S1 subunit of IBV Sczy3 strain, and two mAbs 1D5 and 6A12 were positive in indirect ELISA against both His-S1 protein and the purified whole viral antigen. MAb 6A12 and 1D5 could recognized by other 10 IBV strains (IBVs) from five different genotypes, except that 1D5 had a rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 24 publications
1
12
0
Order By: Relevance
“…This phenomenon may be explained by the existence of common VN epitopes present in different IBV genes. For example, in cK/CH/SCDY/141030 and Sczy3, two common VN epitopes (87PPQGMAW93 and 412IQTRTEP418) (Zou et al, 2015) were observed in the S1 genes of both strains. Although the five VN epitopes in the HVRs were quite different between strains cK/CH/SCDY/141030 and H120, other common VN epitopes may be located in the S2 and N proteins of these two strains, as there are reports that the S2 and N proteins may induce neutralizing reactions (Ignjatovic and Sapats, 2005;Koch et al, 1990).…”
Section: Discussionmentioning
confidence: 99%
“…This phenomenon may be explained by the existence of common VN epitopes present in different IBV genes. For example, in cK/CH/SCDY/141030 and Sczy3, two common VN epitopes (87PPQGMAW93 and 412IQTRTEP418) (Zou et al, 2015) were observed in the S1 genes of both strains. Although the five VN epitopes in the HVRs were quite different between strains cK/CH/SCDY/141030 and H120, other common VN epitopes may be located in the S2 and N proteins of these two strains, as there are reports that the S2 and N proteins may induce neutralizing reactions (Ignjatovic and Sapats, 2005;Koch et al, 1990).…”
Section: Discussionmentioning
confidence: 99%
“…IB is an economically important, highly contagious, acute, upper-respiratory tract disease of chickens and other fowl, caused by the avian coronavirus IBV [31,32]. Although multiple genotypes of IBV have continuously been detected, e.g., QX-type, TW-type, and TC07-2, QX-type IBV is still the prevalent genotype in China [12,15,33]. Therefore, it is important to understand the antigenicity and pathogenicity of QX-type IBV field isolates for the prevention and control of IB.…”
Section: Discussionmentioning
confidence: 99%
“…IBV is a typical coronavirus that is constantly recombining and mutating its antigenicity, leading to the presence of multiple serotypes and genotypes of IBV strains and causing major challenges in disease prevention and control (Cavanagh, 2007). As an important antigenic protein, S1 has been used in vaccine development (Hodgson et al, 2004;Wickramasinghe et al, 2014;Zou et al, 2015). Notably, S2 protein also can induce protective immune responses (Eldemery et al, 2017;Ignjatovic and Sapats, 2005).…”
Section: Discussionmentioning
confidence: 99%